PENGARUH TEKNOLOGI MESIN TERHADAP PERUBAHAN PENGGUNAAN KOSA KATA DI BIDANG PERTANIAN (Sebuah Kajian atas Masyarakat Petani di Kabupaten Blora) - Nurhayati Nurhayati (Master Program in Linguistics, Diponegoro University, 2010)
This paper deals with the use of certain vocabulary in agricultural domains. Some farmers in the district of Blora, Central Java, have no longer used some key vocabulary traditionally used in agricultural practices. Due to the application of modern technology in the ricefields, the farmers get accustomed to new vocabulary representing some modern equipment used in agricultural practices. Not only have the vocabulary of agricultural practices in the ricefield but also those of rice management and of some traditional ceremonies related to farmings changed quite noticeably